Negotiating Religiosity and Cultural Commercialization in the Adaptation of the Halal Industry within Bugis–Makassar Traditional Weddings - Nursakia Nursakia (Jurnal Mahkamah : Kajian Ilmu Hukum dan Hukum Islam, 2026)
Previous studies on Bugis-Makassar weddings have primarily examined the symbolic meanings of customary rituals, while research on the halal industry has generally focused on certification, regulation, and market growth at the macro level. Limited attention has been given to how halal industry practices interact with ritual authority, communal solidarity, and cultural commercialization within local wedding traditions. This study examines the adaptation of the halal industry in Bugis Makassar customary weddings in Soppeng Regency and analyzes the negotiation between Islamic religiosity, customary values, and market practices. Employing a qualitative case study design, data were collected through participant observation, in-depth and semi-structured interviews with wedding service providers, cultural figures, religious leaders, consumers, and a representative of the Halal Product Assurance Organizing Agency, as well as document analysis. The data were analyzed through reduction, display, conclusion drawing, and verification. The findings demonstrate that halal standard implementation operates through a hybrid model combining formal regulatory requirements, self-regulated halalan thayyiban practices, collective trust, and business reputation. The expansion of professional wedding services has shifted the instrumental and technical roles of customary figures, including the Bissu and indo’ botting, to wedding service providers, while authority over sacred rituals and cultural meanings remains under the control of the extended family. The massarapo tradition has also transformed from collective physical labor into financial contributions and vendor-based assistance, indicating a reconfiguration rather than the disappearance of social solidarity. Halal attributes simultaneously function as expressions of religious commitment, service-quality standards, and market differentiation. This study contributes the concept of procedural cultural hybridization to explain how religious standards, market mechanisms, and customary authority are negotiated without completely displacing Bugis Makassar cultural identity.